Kyai's Leadership in Fostering Alumni Harmony and Solidarity through the Halaqah Approach in Islamic Boarding Schools - Annabil, Fatih Shidqi; Hanif, Muh. (Journal of Islamic Education Research, 2025)
The leadership of the kyai in Islamic boarding schools (Pesantren) plays a vital role in fostering alumni harmony and solidarity. This study explores how the halaqah approach (regular spiritual gatherings) serves as a medium through which kyai maintain deep emotional and spiritual ties with alumni. Using a qualitative ethnographic method at Pondok Pesantren Kutasari, Purbalingga, this research reveals that the kyai acts as a unifying figure through participatory and inclusive leadership, encouraging alumni engagement across generations. The findings show that the kyai’s charismatic and spiritual leadership fosters a strong collective identity among alumni, enabling continued collaboration in religious, social, and educational fields. The halaqah is not merely a learning forum but a cultural space for renewing values and reinforcing brotherhood. This highlights how traditional leadership rooted in Islamic values ensures alumni cohesion amid a changing society. Kepemimpinan kyai di pesantren memiliki peran sentral dalam membangun kerukunan dan solidaritas alumni. Studi ini mengkaji bagaimana pendekatan halaqah (forum pengajian rutin) dimanfaatkan oleh kyai untuk menjaga keterikatan emosional dan spiritual dengan alumni. Melalui metode etnografi kualitatif di Pondok Pesantren Kutasari, Purbalingga, ditemukan bahwa kyai berperan sebagai pemersatu melalui gaya kepemimpinan yang partisipatif dan inklusif, mendorong keterlibatan alumni lintas generasi. Temuan menunjukkan bahwa kepemimpinan kyai yang karismatik dan spiritual memperkuat identitas kolektif alumni sehingga memungkinkan kolaborasi berkelanjutan dalam bidang keagamaan, sosial, dan pendidikan. Halaqah tidak hanya menjadi media belajar, tetapi juga ruang budaya untuk memperbarui nilai-nilai dan mempererat ukhuwah. Hal ini menunjukkan bahwa kepemimpinan tradisional berbasis nilai Islam mampu menjaga kohesi alumni di tengah perubahan masyarakat.